Immunological Implications of Gold Weight Implantation for Lagophthalmos: A Systematic Review - Iskandar, Elza; Krisna Murti; Irsan Saleh; Ramzi Amin (HM Publisher, 2024)
Background: Gold weight implantation is a well-established surgical intervention for lagophthalmos, a condition characterized by incomplete eyelid closure. While generally safe and effective, gold implants can elicit immune responses, potentially leading to complications. This systematic review aims to comprehensively evaluate the immunological implications of gold weight implantation in lagophthalmos treatment. Methods: A systematic search of PubMed and ScienceDirect databases was conducted, encompassing studies published from 2000 to June 2024. Keywords included